Networking behaviour, graduate employability: a social capital perspective. Issue 4 (10th April 2017) - Batistic, Saša; Tymon, Alex
Abstract : Purpose: Drawing on the overarching framework of social capital theory, the purpose of this paper is to develop and empirically examine networking behaviour and employability within the higher education context. Design/methodology/approach: In a sample of 376 full-time business students the authors measured perceived employability, networking behaviour, access to information and resources and job-search learning goal orientation (JSLGO). Findings: The authors found networking is related to increased internal and external perceived employability by boosting access to information and resources. The results also demonstrate that networking is positively related to access to information and resources for low and high JSLGO, the relationship being stronger for those with higher levels. Research limitations/implications: The results provide an enriched view of individual networking behaviour by offering an indirect model of networking outcomes and to the graduate employability and social capital literatures. Practical implications: The findings may provide focus for individuals concerned with enhancing their employability and those involved in supporting career guidance. Originality/value: Obvious beneficiaries are students, for whom employment is a key concern, and universities who face increasing pressure to enhance graduate employability whilst resources to do so are diminishing. To this end the authors highlight activities that may develop networking behaviours and JSLGO.